Inexperienced adults’ reliance on extrinsic product attributes to judge the quality of major household appliances - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2013)
Dissertation (M (Consumer Science))--University of Pretoria, 2005.